E F F E C T O F P O LY M E R I C N A N O PA R T I C L E “ P N I PA M ” (POLY-N- ISOPROPYL ACRYAMIDE) ON THE MICROBIAL INFESTATIONS OF TASAR SILKWORM - ROHIT KUMAR VERMA, MD. IMTIYAZ ASLAM, RICHA ROY AND S. P. ROY, (The Bioscan, 2013)
The present paper deals with the use of Polymeric compound such as “PNIPAM” for minimizing the fungal growth on various developmental stages of the wild variety of the Daba ecorace of tropical tasar silkworm, Antheraea mylitta Drury (Lepidoptera: Saturniidae). “PNIPAM” is a nanoparticle and has ability to form a microfilm which is acting as a barrier both externally and internally around the infected silkworms, thus, preventing the microbial infection therein. These nanoparticles have microfilm forming ability and can produce an additional barrier against the microbial infestations. The microbial diseases cause severe loss both in the productivity as well as silk performances parameters. In the present study an attempt has been made to know the efficacy of “PNIPAM”, a polymeric compound for restricting the fungal growth on larval stages of tasar silkworms. It was observed that the formation of microfilms interfered with the growth of fungal infection and finally inhibits the microbial population. It was due to the restricted growth of the fungal hyphae in the microfilm that results in the suppression of mycilial growth both externally and internally body epithelia of the different larval instars. The result indicating that the application of “PNIPAM” at a concentration of 0.4 and 0.6 mg/mL shows significant decrease in microbial infestations in these silkworms. The work will add some valuable breakthrough in minimizing the loss of tasar silk production due to microbial infection, which is a common factor for this wild variety of tasar silkworm